Therapeutic drug monitoring plays an important role in patients with noninfectious uveitis receiving adalimumab - Cheng, Weidong; Xiao, Jiayu; Li, Shengjie; Wang, Huaru; Wang, Shasha; Qian, Yujing; Zhao, Chan; Gao, Fei; Qin, Xuzhen; Zhang, Meifen (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the association between serum adalimumab (ADA) concentrations, antibodies against adalimumab (AAAs), tumor necrosis factor α (TNFα) levels, and clinical response in patients with noninfectious uveitis (NIU), as well as changes in TNFα after administration of ADA, to explore the role of therapeutic drug monitoring in these patients.MethodsThis retrospective study included NIU patients treated with ADA at Peking Union Medical College Hospital between June 2024 and April 2025, who underwent testing for serum ADA and AAA levels. Most patients also had serum TNFα measured concurrently. Clinical data collected included concomitant medications, ADA dosing frequency, and ocular inflammation status, etc. High-performance size-exclusion chromatography was used to characterize forms of TNFα in serum samples of patients. THP-1 cells were stimulated with free TNFα or TNFα-ADA complexes to compare their pro-inflammatory activity.ResultsAmong 164 test results from 147 patients included (aged 5~56 years), median ADA level was significantly lower in AAA-positive patients than in AAA-negative patients (1.9 vs. 6.4 μg/mL; P<0.001), and lower in those with active inflammation than in those with quiescent inflammation (2.2 vs. 6.0 μg/mL; P<0.001). An ADA level below 4.1 μg/mL was associated with poor clinical response. Concomitant antimetabolite use was linked to a lower proportion of detectable AAAs compared with ADA monotherapy (34.3% vs. 54.5%; P = 0.036). Median ADA level was significantly higher when testing occurred ≤14 days after the last dose of ADA (P<0.001), though many patients maintained therapeutic levels even with extended dosing intervals. TNFα levels increased in most patients after ADA therapy, predominantly in the form of TNFα-ADA complexes, which exhibited significantly weaker pro-inflammatory effects than free TNFα.ConclusionThe presence of AAAs was associated with reduced ADA levels and an increased risk of treatment failure. Despite the limitations of a retrospective design, these findings suggest that therapeutic drug monitoring may help identify causes of treatment failure and optimize regimens in stable patients.